The Interaction Between Environmental Sanitation and Pregnant Women's Nutritional Intake on the Risk of Stunting in Toddlers - Khusnul Nikmah; Ida Susila (Universitas Nahdlatul Ulama Surabaya, 2026)
Stunting is a chronic nutritional problem that impacts the physical growth and development of children. Environmental sanitation factors and maternal nutritional intake during pregnancy play a crucial role in determining toddlers' nutritional status. This study analyzes the relationship between environmental sanitation and pregnant women's nutritional intake on the incidence of stunting in toddlers. In addition, their interactions with stunting incidence. The study used an analytical observational design with a cross-sectional approach. The study population comprised families with toddlers aged 6–59 months. A sample of 100 families was selected using a purposive sampling technique. Data were collected through structured questionnaires, mother interviews, sanitation observations, and height measurements for height-for-age using WHO standards to assess stunting incidence. Data analysis used univariate analysis, the Chi- Square Test for bivariate analysis, and logistic regression to examine variable interactions. Results showed that 38% of toddlers experienced stunting, 45% of families had poor environmental sanitation, and 42% of pregnant women had inadequate nutritional intake. There was a significant correlation between environmental sanitation and the incidence of stunting (p=0.001) and between pregnant women's nutritional intake and stunting (p=0.003). The logistic regression analysis showed that toddlers exposed to poor sanitation and inadequate nutritional intake during pregnancy had a 3.2 times higher risk of stunting than those exposed to only one factor. Stunting is a multifactorial problem influenced by poor sanitation and inadequate maternal nutritional intake during pregnancy. Therefore, efforts to prevent stunting need to be integrated through improving environmental sanitation and enhancing the nutritional quality of pregnant women.